2018
DOI: 10.1007/s00384-018-2977-y
|View full text |Cite
|
Sign up to set email alerts
|

Extralevator versus standard abdominoperineal excision in locally advanced rectal cancer: a retrospective study with long-term follow-up

Abstract: We found a non-significant tendency to lower rates of IOP and positive CRM as well as lower rate of LR in the ELAPE group. Long-term survival and adverse events did not differ between the groups. ELAPE is beneficial for the surgeon in offering better vicinity to the perineal area and better work ergonomics. These technical aspects and the clinically very important tendency to lower rate of LR support the use of ELAPE technique in spite of the lack of survival benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 36 publications
0
14
0
1
Order By: Relevance
“…Pooled data from nine studies [14,17,23,2630,32] that reported operating time showed significantly longer operating time for ELAPE than APE (MD = 57.05, 95% CI = 28.61–85.48, P < 0.001, Table 2) with high heterogeneity ( P < 0.001, I 2 = 90%). The subgroup analysis revealed ELAPE has longer operating time in Europe ( P < 0.001, I 2 = 87%), and no significant statistically difference in Asia ( P = 0.13, I 2 = 92%).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Pooled data from nine studies [14,17,23,2630,32] that reported operating time showed significantly longer operating time for ELAPE than APE (MD = 57.05, 95% CI = 28.61–85.48, P < 0.001, Table 2) with high heterogeneity ( P < 0.001, I 2 = 90%). The subgroup analysis revealed ELAPE has longer operating time in Europe ( P < 0.001, I 2 = 87%), and no significant statistically difference in Asia ( P = 0.13, I 2 = 92%).…”
Section: Resultsmentioning
confidence: 99%
“…Pooled data from eight studies [14,15,17,23,26,27,29,32] that reported estimated blood loss showed lower blood loss for ELAPE than APE (MD = −82.98, 95% CI = −122.06 to −43.90, P < 0.001, Table 2) with high heterogeneity ( P < 0.001, I 2 = 72%). The subgroup analysis revealed ELAPE has lower blood loss in Europe ( P = 0.002, I 2 = 59%) and Asia ( P = 0.008, I 2 = 59%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They noted significantly better circumferential margin status in the ELAPR group, with no difference in intraoperative tumor perforation or other complications (32). Additionally, Carpelan et al compared their APR cohort (27 patients, years 2004-2009) with ELAPR patients (42 patients, years 2009-2016) and noted no significant differences between the groups (33). There was, however a trend toward improved circumferential margin, decreased intraoperative perforation and lower rates of local recurrence in the ELAPR cohort.…”
Section: Discussionmentioning
confidence: 97%